Career construction theory: tools, interventions, and future trends - Wang, Danqi; Li, Yanling (Frontiers in Psychology, 2024)
With the emergence of the borderless career era in the 21st century, career coaching has experienced a change from career guidance and career education to career counseling. Career construction theory has been widely used in career counseling and has substantial application value. Introducing career construct theory’s assessment tools and intervention strategies is necessary and meaningful. In this mini-review, the qualitative assessment tools and intervention approaches of career construct theory are introduced and analyzed; the qualitative assessment tools include the Career Construction Interview and “My Career Story” workbook, and the intervention approaches include the Computer-Assisted Career Counseling System, workshops, group counseling, and individual counseling. Finally, future research directions are proposed, including an analysis of what kinds of career construction interventions are most effective for which groups and under what conditions, career intervention in the digital age, and the standardization of assessment tools. The novelty of this paper lies in the fact that it purposefully proposes future directions for career construction theory from the perspectives of assessment tools and intervention approaches and that research on the assessment tools and intervention approaches of career construction theory still needs further attention.